Aspiration after Anesthesia: Chemical versus Bacterial, Differential Diagnosis, Management, and Prevention - Battaglini, Denise; De Rosa, Silvia (Seminars in Respiratory and Critical Care Medicine, 2024)
Aspiration following anesthesia is a major patient issue and a difficulty for anesthesiologists. Aspiration syndromes are more common than anticipated, and the condition is frequently undetected. Clinical signs are often dictated by the characteristics of aspiration, such as the infectivity of the material, its volume, and the severity of the underlying clinical condition. Pulmonary aspiration can cause an acute or persistent inflammatory response in the lungs and upper airways that can be complicated by tracheobronchitis, aspiration pneumonia, aspiration pneumonitis, acute respiratory distress syndrome, and subsequent bacterial infection due to particle, acid, and bacteria-related processes. Aspiration during anesthesia, while relatively rare, poses significant risks for patient morbidity and mortality. Chemical and bacterial aspiration provide distinct diagnostic and management issues. Preventive strategies such as a complete preoperative risk assessment, adherence to fasting rules, proper patient positioning, and the use of protective airway devices are critical in reducing aspiration risk. In addition, drugs such as proton pump inhibitors can help lower stomach acidity and volume. Innovations in monitoring techniques, better training, and awareness activities are critical to enhancing aspiration event management. Given the importance of this entity, this narrative review sought to make an updated overview of the management of aspiration after anesthesia: chemical versus bacterial, differential diagnosis, management, and prevention.
Keywords: aspiration; anesthesia; pneumonia; bacteria; antibiotics; pulmonary aspiration